STUDENTS' PERCEPTIONS AND MOTIVATIONS OF URBAN AGRIPRENEURSHIP INTERESTS - Putra, Andika Kyo; Hidayat, Syarif Imam; Indah, Pawana Nur (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to: Analyze students' perceptions and motivations towards urban Agripreneurship interests. The population in the study is active students of the Agribusiness Study Program, Faculty of Agriculture, UPN